Pastorale terapie aan die persoon bo tagtig jaar - De Wet, Roelof (University of the Free State, 2010)
Chapter 1 of this study focuses on the growing numbers of older persons and the corresponding pastoral-therapeutic implications. Progressive developments in medical research and treatment and socio-economical change offer persons older than 65 a longer life expectancy and enable them to remain active for a longer period. The demographical implication is that persons in this age group form a larger proportion of populations across the world. These worldwide trends are also evident among all population groups in South Africa with comprehensive consequences in all areas of life, in particular also in respect of the pastoral care and spiritual well-being of the aged. The largest proportional increase in numbers is in the age group above 80. This population segment also includes the largest number of frail elderly persons, who have a special need of pastoral therapeutic support and involvement. In the context of developments in Practical Theology special reference is made to the effects of a hermeneutic approach manifested in post-modern and post-foundationalist paradigms. A diaconiological frame of reference is maintained in the discussion of basistheoretical, meta-theoretical and practical-theoretical methods of approach. In research studies of meetings with elderly residents, based on participative action research, observations are made using the different pastoral-therapeutic approaches as lenses. In chapter 2 the historical development of hermeneutic theory leading to the construction of a hermeneutic paradigmatic frame is pursued. Pastoral-therapeutic implications of a hermeneutic paradigm, which include a systemic and narrative approach, are critically considered. Metatheoretical psychotherapeutic narrative methods and pastoral therapeutic models, which represent different emphases, are critically evaluated from a diaconiological position. In chapter 3 metatheoretical gerontological and psychological scientific contributions are discussed. Residents in a retirement village who wish to receive pastoral therapy are involved in practical applications. The circumstances and views of residents were solicited in a general opinion survey. Basis-theoretical points of departure are elucidated with reference to the pastoraltherapeutic models of Louw and Gerkin. Basic-theoretical and other practical theological points of departure are applied as lenses in participative action research. Practical theoretical pastoral therapeutical approaches are introduced in chapter 4 with special reference to the practice-theory-practice spiralling model of Müller. This is followed by research reports of meetings with persons older than 80, in which perspectives that arose from views through the different practical-theological lenses are given. Perspectives gleaned from the different approaches enhanced the value of results separately and jointly. Contemplation of the Christian truths of salvation and particularly the comfort of eschatological promise afforded basis-theoretical opportunities for the affirmation of faith. Memories from the respondents’ own life stories, in particular of the experience of weakness, pain and dependency, could be placed in the context of the Grand Narrative in the process of therapeutic narrative involvement. The metatheoretical gerontological and psychological lenses contributed valuable perspectives to the experience of later old age, leading to meaningful pastoral-therapeutic application. A better understanding of the need for spiritual growth and the achievement of integrity through self-acceptance and gerotranscendancy could be gained. Psychotherapeutic narrative methods such as deconstruction, externalization and unique outcomes could be applied with good outcomes in a diaconiological scriptural normative approach. Through the application of a practicaltheoretical spiralling practice-theory-practice lens special value could be added by close integration of the own story with the story of the Bible. Although behavioural changes in older persons who have set thinking patterns are difficult to achieve, limited success was achieved in the positive handling of mutual relations of inmates and influencing their actions. The most beneficial pastoral-therapeutical effects were probably achieved in respect of the integration of memories of life, which surfaced in stories told in conjunction with the reality of Christian experience at this late stage of life.

In hierdie studie word gefokus op die groeiende getalle bejaarde persone en die pastoraalterapeutiese implikasies wat dit inhou. Die vooruitgang op mediese gebied en sosioekonomiese ontwikkelinge bied aan persone bo 65 jaar ‘n langer lewensverwagting en stel hulle in staat om tot op ‘n hoër ouderdom aktief te bly. Demografies beteken dit dat bejaardes ‘n groter proporsie van bevolkings oor die wêreld uitmaak. Hierdie wêreldwye tendense is ook in Suid-Afrika onder alle bevolkingsgroepe merkbaar met omvangryke implikasies op alle lewensterreine, en in die besonder ook op die gebiede van pastorale sorg en geestelike welsyn. Persone in die ouderdomsgroep bo 80 vorm die segment waar die groeiende getalle proporsioneel die hoogste is. Terselfdertyd sluit hierdie groep die meeste verswakte bejaardes in met besondere behoeftes aan pastoraal-terapeutiese ondersteuning en betrokkenheid. Ontwikkelinge op die gebied van die Praktiese Teologie word nagegaan met besondere verwysing na die effek van ‘n hermeneutiese benadering in die lig van postmoderne en “postfoundationalist”-paradigmas. Basisteoretiese, praktykteoretiese en metateoretiese uitgangspunte word aangedui as navorsingslense soos aangewend vanuit ‘n diakoniologiese posisionering. Die bedoeling is om pastorale terapie aan persone bo 80 deur hierdie prakties-teologiese uitgangspunte te bestudeer. In hoofstuk 2 word die historiese ontwikkeling van hermeneutiese teorie wat lei tot die vorming van ‘n hermeneutiese denkraamwerk nagegaan. Die pastoraal-terapeutiese implikasies van ‘n hermeneutiese paradigma, met insluiting van ‘n sistemiese benadering en die aanwending van die narratief en storievertelling word krities ondersoek. Metateoretiese psigoterapeutiese narratiewe metodes en pastoraal-terapeutiese modelle wat verskillende prakties-teologiese aksente verteenwoordig, word vanuit ‘n diakoniologiese posisionering beoordeel. In hoofstuk 3 word metateoretiese gerontologiese en psigologiese uitgangspunte in oënskou geneem. In die praktyktoepassing word gefokus op persone woonagtig in ‘n aftreeoord vir bejaardes. Inwoners se omstandighede en sienings word in ‘n meningsopname verken. Basisteoretiese uitgangspunte word bespreek met verwysing na die modelle van Louw en Gerkin. Hierdie en ander prakties-teologiese uitgangspunte word as lense toegepas in deelnemendeaksienavorsing. In hoofstuk 4 word praktykteoretiese pastoraal-terapeutiese benaderings aan die orde gestel met besondere verwysing na Müller se praktyk-teorie-praktyk-spiralende model. Verdere navorsingsverslae van ontmoetings met persone bo 80 volg, soos gesien deur die verskillende prakties-teologiese lense. Die verskillende perspektiewe bied waardevolle aanvullende en verhelderende uitkomste. Basisteoreties verleen die herbesinning oor Christelike heilswaarhede en in besonder die troos van ‘n eskatalogiese uitsig opnuut die geleentheid tot geloofsbevestiging. Deur terapeutiese narratiewe betrokkenheid word herinneringe uit die eie lewensverhaal, en in die besonder die realiteit van die belewenis van swakheid, pyn en afhanklikheid, in die konteks van die Groot Verhaal geplaas. Die metateoretiese gerontologiese en psigologiese lens voeg waardevolle perspektiewe tot die belewing van die hoër ouderdomsfases toe, wat tot sinvolle pastoraal-terapeutiese aanwending bydra. Insig is toegevoeg tot die verstaan van die behoefte aan geestelike verdieping en die bereiking van integriteit in eie lewe deur selfaanvaarding en gerotransendensie. Psigoterapeutiese narratiewe metodes soos dekonstruksie, eksternalisering en unieke uitkomste is met vrug binne ‘n diakoniologiese skriftuurlik-normatiewe benadering aangewend. ‘n Praktykteoretiese spiralende praktyk-teorie-praktyklens het besondere waarde toegevoeg deur nuwe perspektiewe tot die verstaan en interpretasie van die storie te open, gespieël in die verhaal van die Bybel. Hoewel gedragsveranderinge by ouer persone met vasgelegde denkpatrone moeilik haalbaar is, is daar tog ‘n mate van sukses behaal in die positiewe hantering van onderlinge verhoudings en beïnvloeding ten opsigte van optrede. Die voordeligste pastoraal-terapeutiese effekte is waarskynlik behaal in die integrasie van herinneringe soos dit in lewensverhale na vore gekom het, met die realiteit van die Christelike belewenis op hierdie laat stadium van die lewe.
Thesis (Ph.D. (Practical Theology))--University of the Free State, 2010
Keywords: Older people -- Pastoral counseling of; Church work with older people; Metatheoretical viewpoint; Basis-theoretical viewpoint; Hermeneutical pastoral approach; Diaconiological approach; Narrative pastoral approach; Participation action research; Persons older than 80; Practical theological approaches; Pastoral therapy; The aged